Motor vehicle collisions involving adult pedestrians in eThekwini in 2007 - Hobday, Michelle; Knight, S. (Taylor & Francis, 2010)
Motor vehicle collisions involving adult pedestrians are an important cause of injury in South Africa. Using the eThekwini Transport Authority Database for 2007, the data about collisions involving pedestrians over the age of 15 years in the eThekwini metropolitan area were analysed. The incidence risk and proportions were calculated for risk factors involving pedestrians, drivers and the environment. Male pedestrians aged 25-34 years were at highest risk of injury compared to other male pedestrians (incidence risk ratio (IRR): 1.36; 95% confidence interval (CI): 1.26-1.48). The group with the highest fatality risk was males aged 50-54 years (IRR: 1.67; 95% CI: 1.04-2.67). Male drivers had a greater than seven times risk of involvement in pedestrian collisions when compared to females. The highest proportion of fatal pedestrian collisions involved trucks, occurred on freeways, in wet conditions and at night in unlit conditions. The findings point to the need to (a) improve pedestrian visibility and (b) implement engineering interventions to protect adult pedestrians. Enforcement should target high-risk drivers and pedestrians. For the first time in research involving road traffic injuries, this study provides an overall picture of both fatal and non-fatal pedestrian collisions in a South African municipality. © 2010 Taylor & Francis.